STUDY OF INTROGRESSIVE LINES OF COMMON WHEAT WITH Aegilops tauschii GENETIC MATERIAL FOR RESISTANCE TO LEAF RUST - E. R. Davoyan; D. S. Mikov; Y. S. Zubanova; D. M. Boldakov; R. O. Davoyan; I. V. Bebyakina; V. А. Bibishev (Вавиловский журнал генетики и селекции)
The synthetic forms of Triticum miguschovae (GGAADD), Triticum palmovae (AbAbDD), T. durum (M. it.)/Ae. Tauschii (BBAADD) and the introgressive lines of common wheat created on their basis were evaluated for resistance to leaf rust. All synthetic forms have a high resistance to leaf rust. Twenty-two lines of common wheatresistant to leaf rust with genetic material from T. miguschovae, 10 lines with genetic material from T. durum (M. it.)/Ae. tauschii and 4 lines obtained on the basis of T. palmovae were identified. A screening with the use of molecular markers for the presence of leaf rust resistance genes Lr21, Lr26, Lr32, Lr39 was done. The GDM35 marker linked to the Lr39 gene was identified in the synthetic forms. Molecular markers Lr21F/R and BARC135 linked to the genes Lr21 and Lr32, respectively, were not identified. Resistance to leaf rust in lines 729, 1555, 2203, 2289, 2295, 2296, 4155, 4171, obtained on the basis of T. miguschovae, lines 3261, 3265, obtained on the basis of T. palmovae, and in line 4141 with the genetic material from T. durum (M. it.)/Ae. Tauschii is controlled by the presence of the Lr39 gene. The SCM9 marker indicating the presence of translocation of 1BL.1RS with the Lr26 gene was detected in 15 lines obtained on the basis of T. miguschovae, in 2 lines with genetic material from T. durum (M. it.)/Ae. tauschii, and in 1 line created on the basis of T. palmovae. Lines 729, 1555, 2203, 2289, 2295, 2296, 4155, 4171 obtained with the participation of T. miguschovae and line 3261 with the participation of T. palmovae carry a combination of genes (Lr39+Lr26).